Chelating phosphane-boranes as hemilabile ligands - Synthesis of [Mn(CO)3(eta(2)-H3B center dot dppm)][BAr4F] and [Mn(CO)(4)(eta(1)-H3B center dot dppm)][BAr4F] - Merle, N; Frost, C; Kociok-Koehn, G; Willis, M; Weller, A (2006)
Manganese complexes bearing the chelating phosphaneborane ligand H 3B·dppm [dppm = bis(diphenylphosphanyl)-methane] have been prepared. Addition of H3B·dppm to Mn(CO)5Br using Na[BArF4] as a halide-abstracting reagent affords [Mn(CO)3(η2-H3B·dppm)][BAr F4] (1). This reacts with CO to open the bidentate borane to afford [Mn(CO)4(η1-H3B·dppm)] [BArF4] (2) in which the borane is now bound in a monodentate manner. The CO addition is reversible, and placing 2 under vacuum (hours) regenerates 1 quantitatively, demonstrating that the chelating phosphane-boranes can act as hemilabile ligands. The complexes 1 and 2 have been fully characterised by NMR spectroscopy and X-ray crystallography. © Wiley-VCH Verlag GmbH and Co. KGaA, 2006.